Biliary Epithelial Senescence in Liver Disease: There Will Be SASP - Meadows, Vik; Baiocchi, Leonardo; Kundu, Debjyoti; Sato, Keisaku; Fuentes, Yessenia; Wu, Chaodong; Chakraborty, Sanjukta; Glaser, Shannon; Alpini, Gianfranco; Kennedy, Lindsey; Francis, Heather (Frontiers in Molecular Biosciences, 2021)
Cellular senescence is a pathophysiological phenomenon in which proliferative cells enter cell cycle arrest following DNA damage and other stress signals. Natural, permanent DNA damage can occur after repetitive cell division; however, acute stress or other injuries can push cells into premature senescence and eventually a senescence-associated secretory phenotype (SASP). In recent years, there has been increased evidence for the role of premature senescence in disease progression including diabetes, cardiac diseases, and end-stage liver diseases including cholestasis. Liver size and function change with aging, and presumably with increasing cellular senescence, so it is important to understand the mechanisms by which cellular senescence affects the functional nature of the liver in health and disease. As well, cells in a SASP state secrete a multitude of inflammatory and pro-fibrogenic factors that modulate the microenvironment. Cellular SASP and the associated, secreted factors have been implicated in the progression of liver diseases, such as cholestatic injury that target the biliary epithelial cells (i.e., cholangiocytes) lining the bile ducts. Indeed, cholangiocyte senescence/SASP is proposed to be a driver of disease phenotypes in a variety of liver injuries. Within this review, we will discuss the impact of cholangiocyte senescence and SASP in the pathogenesis of cholestatic disorders.